2023
DOI: 10.21203/rs.3.rs-2625958/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 (angiotensin converting enzyme) polymorphisms and susceptibility of severe SARS- CoV-2 in subset of Pakistani population

Abstract: Science is digging for the varied presentation of COVID-19 patients exposed to the same risk factors, and medical conditions may be influenced by the presence of polymorphic genetic variants. This study investigated the link between ACE2 gene polymorphisms and the severity of SARS-Cov-2. This cross-sectional study recruited COVID-19 PCR-positive patients by consecutive sampling from Ziauddin Hospital from April to September 2020. DNA was extracted from whole blood, followed by gene amplification and Sanger’s s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Laboratory data from our patients and fndings from further research revealed that patients with severe and critical illness had considerably higher levels of CRP, Ddimer, and serum ferritin compared to mild/moderate cases (Tables S1 and S2) [27,28]. In addition, Gómez-Haranz et al…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Laboratory data from our patients and fndings from further research revealed that patients with severe and critical illness had considerably higher levels of CRP, Ddimer, and serum ferritin compared to mild/moderate cases (Tables S1 and S2) [27,28]. In addition, Gómez-Haranz et al…”
Section: Discussionmentioning
confidence: 63%
“…Laboratory data from our patients and findings from further research revealed that patients with severe and critical illness had considerably higher levels of CRP, D-dimer, and serum ferritin compared to mild/moderate cases (Tables S1 and S2 ) [ 27 , 28 ]. In addition, Gómez-Haranz et al reported significant correlations between case severity and different laboratory markers, including CRP, D-dimer, and ferritin levels [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations